Study of the absorption band in the range 0.3-0.9 eV inherent to solid solutions p-Ge₁₋xSix irradiated by fast electrons at the temperature 77 K - Abbasov, Sh.M.; Agaverdiyeva, Y.T.; Kerimova, T.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
Ge₁₋xSix solid solutions are one of promissing materials for semiconductor technique. However, their electrical and optical properties, especially with silicon content more than 5 at. % have been little studied. In particular, in the number of works [1-3] there have been presented the experimental results of study in the region 0.52 eV in germanium irradiated by fast electrons, gamma-rays and protons at the temperature of liquid nitrogen. In the literature, however, there are no data on studying the absorption band in the range 0.52 eV in Ge₁₋xSix solid solution irradiated by fast electrons.